Extremely Active Ethylene Tetramerization Catalyst Avoiding the Use of Methylaluminoxane: [iPrN{P(C6H4-p-SiR3)2}2CrCl2]+[B(C6F5)4]− - Park, Hee Soo; Kim, Tae Hee; Baek, Jun Won; Lee, Hyun Ju; Kim, Tae Jin; Ryu, Ji Yeon; Lee, Junseong; Lee, Bun Yeoul (ChemCatChem, 2019)
Sasol's original ethylene tetramerization catalyst requires the use of expensive MMAO, a low working temperature (∼60 °C), and generates polyethylene (PE) as a side product. In this study, we developed an upgraded catalytic system that successfully avoids the need for MMAO. [(PNP)CrCl2]+[B(C6F5)4]−-type species was obtained from the reaction of CrCl3(THF)3, [PhN(H)Me2]+[B(C6F5)4]−, and iPrN[P(C6H4-p-Si(nBu)3)2]2 (2) as well as from simply reacting 2 with [CrCl2(NCCH3)4]+[B(C6F5)4]−. The bulky (nBu)3Si-substituents play the crucial role of preventing the formation of the inactive [(PNP)2CrCl2]+[B(C6F5)4]−. The prepared [2-CrCl2]+[B(C6F5)4]− combined with iBu3Al was extremely active ('4000 kg/g-Cr/h), performed well at a high temperature of up to 90 °C, and generated a negligible amount of PE (0.03 wt%). Screening the performance with a series of iPrN[P(C6H4-p-SiR3)2]2 further supported that bulky R3Si-substituents are crucial not only to achieve extremely high activities but also to minimize the generation of PE. Structure of a [(PNP)CrCl2]+[B(C6F5)4]− species was elucidated by X-ray crystallography.
Keywords: 1-octene; Active ethylene; Catalytic system; High temperature; Methylaluminoxane; Phosphane ligands; Tetramerization; Working temperatures; 1-octene production; chromium; ethylene tetramerization; oligomerization; phosphane ligands